2019
DOI: 10.1111/jth.14626
|View full text |Cite
|
Sign up to set email alerts
|

Transgender patients and the role of the coagulation clinician

Abstract: The medical care of transgender patients relies on the use of sex hormones to develop and maintain the physical characteristics consistent with gender identity as the first step in transitioning. Hormonal therapy is usually continued indefinitely, even following gender‐affirming surgeries. The use of hormonal treatments is associated with a multitude of positive effects as well as complications and side effects. The risk of venous thromboembolism (VTE) is a major concern. Transgender patients are often referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…30 More recently, the Registro Informatizado de Enfermedad TromboEmbólica (Computerized Registry of Patients with Venous Thromboembolism) investigators reported a 2-year VTE recurrence rate of 3.3% for women whose initial event was pregnancy (or postpartum) associated. 31 Collectively, these data suggest that limited duration anticoagulation may be appropriate for most women with prior pregnancy-associated VTE, after close follow-up and personalized assessment of risk factors as outlined in Figure 2.…”
Section: Vte Recurrence Risk In Women Whose Initial Vte Event Was Promentioning
confidence: 89%
“…30 More recently, the Registro Informatizado de Enfermedad TromboEmbólica (Computerized Registry of Patients with Venous Thromboembolism) investigators reported a 2-year VTE recurrence rate of 3.3% for women whose initial event was pregnancy (or postpartum) associated. 31 Collectively, these data suggest that limited duration anticoagulation may be appropriate for most women with prior pregnancy-associated VTE, after close follow-up and personalized assessment of risk factors as outlined in Figure 2.…”
Section: Vte Recurrence Risk In Women Whose Initial Vte Event Was Promentioning
confidence: 89%
“…A recent retrospective cohort study showed no cases of VTE among TGD adolescents on testosterone therapy in one clinical setting 20. Overall, conclusions from the literature regarding testosterone therapy have been conflicting, and case reports for the adolescent TGD population may suggest an association of testosterone and VTE 21–23. Among adolescents, one case report describes a 17-year-old transgender male receiving masculinizing therapy for male gender affirmation who presented with bilateral pulmonary emboli 21.…”
Section: Discussionmentioning
confidence: 99%
“…On the risk of venous and arterial thrombotic events in transmen (persons born with female sex assigned and male gender identity) who use testosterone as gender‐affirming hormone therapy, only few data are available 31,33‐35 . In the available studies, there does not seem to be an increased risk of thrombotic events compared with control ciswomen (persons born with female sex assigned at birth and a female gender identity) 31,33,34 .…”
Section: Influence Of Sex Hormonesmentioning
confidence: 99%